Relationship between ACTN3 R577X polymorphism and maximal power output in elite Polish athletes - Orysiak, J.; Busko, K.; Michalski, R.; Mazur-Rózycka, J.; Gajewski, J.; Malczewska-Lenczowska, J.; Sitkowski, D.; Pokrywka, A. (Medicina, 2014)
The main purpose of this study was to examine the association between ACTN3 R577X polymorphism and the ability to produce peak power in young male athletes from various sports. Our hypothesis was that the ACTN3 R577X polymorphism is associated with jumping performance and athletes with RR genotype have better scores in tests than athletes with XX or RX genotype independently of the sport discipline. Two hundred young Polish male participants representing different disciplines were recruited for this study. Genotyping for ACTN3 gene was performed using polymerase chain reaction. The power output of lower extremities and the height of rise of the body mass center during vertical jumps were measured on a force plate. The genotype distribution of the ACTN3 gene did not differ significantly between groups of athletes. The significant difference in height of counter-movement jump was found between athletes with RR and XX genotype (0.446±0.049m vs. 0.421±0.036m, respectively, P=0.026). The ACTN3 RR genotype was associated with greater muscle power and height of jump in young male athletes. These results suggest that the ACTN3 gene may play a significant role in determining muscle phenotypes. However, this gene is only one of many factors which could contribute to athletes` performance and muscle phenotypes.